1.упростить:

-6-2(2-у)-2у+2

2.Выразите величину А из формулы Т=An+v

3.Преобразуйте в многочлен выражение:

-(b-2)(b+2)-2(b+4)(b+2)

4.Разложите на множители:

3x^2-6xm-9m^2

5.Упростите:

a+x x- a^2 a

(_____ - ______)* ______ : ____

a x x^2+ay 8x

2

Ответы и объяснения

2012-04-14T14:09:43+00:00
Лучший Ответ!
2012-04-14T14:11:10+00:00

1. -6-2(2-y)-2y+2 = -6-4+2y-2y+2=-8

2. A = (T-v)/n

3. -(b-2)(b+2)-2(b+4)(b+2) = -b^2 + 4 - 2b^2 - 12b - 8 = -3b^2 - 12b -4

4.3x^2 - 6xm - 9m^2 = 3x^2 - 9xm + 3xm - 9m^2 = 3(x+m)(x-3m)

5. Неразборчиво написано!